Electro‐oxidation of phenol in petroleum wastewater using a novel pilot‐scale electrochemical cell with graphite and stainless‐steel electrodes - Abou‐Taleb, Enas M.; Hellal, Mohamed S.; Kamal, Kholod H. (Water and environment journal : WEJ, 2021)
This work investigated the removal of phenol from petroleum wastewater by the electro‐oxidation process. The experimental design was developed on a pilot‐scale electro‐oxidation system equipped with a cylindrical shape of graphite electrodes as an anode and stainless‐steel electrodes as a cathode. An initial study was performed based on operating variables such as current density and time on real petroleum wastewater. The optimum conditions were obtained as a current density of 3 mA/cm2 and time 15 min. Under these applied optimum conditions, complete phenol removal from an initial concentration of about 6.8 mg/L was achieved. Also, 50–60% removal of organic matter in terms of chemical oxygen demand (COD) and biological oxygen demand (BOD). The removal of organic matter using electro‐oxidation requires a long reaction time. Also, the economic study indicated that the energy consumption was determined to be 0.79 kWh/m3 and the operating cost was 0.051 $/m3 which is very economical compared with conventional methods.